ALTC Assessment : Completed and Continuing Projects and Fellowships Related to Assessment 2010. (Office for Learning and Teaching, 2010)
This report is a list of completed and continuing projects from the Australian Learning and Teaching Council. When the Australian Learning and Teaching Council (ALTC) started operations in 2005, academic standards, assessment practices and reporting were among the ALTC's designated responsibilities and priorities as determined by the ALTC Board. Over the years, the number of projects and fellowship programs focusing on assessment has grown substantially and this remains one of the priority areas that attracts a significant number of applications with each new funding round. This report outlines each 2010 ALTC-funded project and fellowship with a focus on assessment. It includes both completed and ongoing projects and fellowships.